Wei 2011 Analysis of Varved Sediment and Weather Relationships in Lake Linné, Svalbard - ACADIS Community Support (Arctic Data Center, 2013)
Abstract: The debate involving climate change has become increasingly important in the recent decade. Arctic environments are important locations for study as they are particularly sensitive to climate variations. Proglacial lake sediments, particularly varves, such as those found at Lake Linné, on the island of Spitsbergen, Svalbard, demonstrate this sensitivity as they are driven by glacial ablation. The correlation of cores from different locations in Lake Linné has served to address inconsistencies in the varve record across the lake. The relationship between measured varve thickness and weather parameters is based on meteorological records for the past century, and demonstrates the responsiveness of varves to changes in climate and weather. The strongest relationships between varves and weather were between positive degree estimates and varve thicknesses. Proximal locations showed the strongest values (r-squared = 0.331), while summer thickness measurements at an intermediate deep basin site correlated best with the past two decades (r-squared = 0.45). The measuring and counting of varves allowed the construction of a chronology that then serves as a climate proxy for Svalbard for the past century. The varve analysis from this study reveals the complexity of the sedimentation in Lake Linné, and it attempts to define the other likely factors that contribute to varve deposition. Overall, the assembled climate relationships reveal varves which can be linked to changes in weather and climate patterns, and a response of the Lake Linné proglacial system in the last two decades to climate change.